Validity of claims‐based algorithms to identify neurodevelopmental disorders in children. Issue 12 (15th October 2021) - Straub, Loreen; Bateman, Brian T.; Hernandez‐Diaz, Sonia; York, Cassandra; Zhu, Yanmin; Suarez, Elizabeth A.; Lester, Barry; Gonzalez, Lyndon; Hanson, Ryan; Hildebrandt, Clara; Homsi, Joseph; Kang, Daniel; et al.
Abstract: Purpose: To validate healthcare claim‐based algorithms for neurodevelopmental disorders (NDD) in children using medical records as the reference. Methods: Using a clinical data warehouse of patients receiving outpatient or inpatient care at two hospitals in Boston, we identified children (≤14 years between 2010 and 2014) with at least one of the following NDDs according to claims‐based algorithms: autism spectrum disorder/pervasive developmental disorder (ASD), attention deficit disorder/other hyperkinetic syndromes of childhood (ADHD), learning disability, speech/language disorder, developmental coordination disorder (DCD), intellectual disability, and behavioral disorder. Fifty cases per outcome were randomly sampled and their medical records were independently reviewed by two physicians to adjudicate the outcome presence. Positive predictive values (PPVs) and 95% confidence intervals (CIs) were calculated. Results: PPVs were 94% (95% CI, 83%–99%) for ASD, 88% (76%–95%) for ADHD, 98% (89%–100%) for learning disability, 98% (89%–100%) for speech/language disorder, 82% (69%–91%) for intellectual disability, and 92% (81%–98%) for behavioral disorder. A total of 19 of the 50 algorithm‐based cases of DCD were confirmed as severe coordination disorders with functional impairment, with a PPV of 38% (25%–53%). Among the 31 false‐positive cases of DCD were 7 children with coordination deficits that did not persist throughout childhood, 7 with visual‐motor integration deficits, 12 with coordination issues due to an underlying medical condition and 5 with ADHD and at least one other severe NDD. Conclusions: PPVs were generally high (range: 82%–98%), suggesting that claims‐based algorithms can be used to study NDDs. For DCD, additional criteria are needed to improve the classification of true cases.